2015
DOI: 10.1002/adsc.201500313
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium(I)‐Catalyzed Intermolecular Hydroacylation of α‐Keto Amides and Isatins with Non‐Chelating Aldehydes

Abstract: The application of the bidentate, electron-rich bisphosphine ligand, 1,3-bis(dicyclohexyl)phosphine-propane (dcpp), in rhodium(I)-catalyzed intermolecular ketone hydroacylation is herein described. Isatins and α-keto amides are shown to undergo hydroacylation with a variety of non-chelating linear and branched aliphatic aldehydes. Also reported is the synthesis of new bidentate chiral phosphine ligands, and their application in hydroacylation is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 64 publications
0
12
0
1
Order By: Relevance
“…Achiral Rh(I) catalysts were later applied to the synthesis of racemic products to expand upon the types of α -ketoamides, isatins and α -branched aldehydes that could be employed. 77 …”
Section: Ketonesmentioning
confidence: 99%
See 1 more Smart Citation
“…Achiral Rh(I) catalysts were later applied to the synthesis of racemic products to expand upon the types of α -ketoamides, isatins and α -branched aldehydes that could be employed. 77 …”
Section: Ketonesmentioning
confidence: 99%
“…Upon investigating aldehyde scope, the authors established that a number of alkyl derivatives were competent C–H bond activation substrates, with linear, α- and β-branched derivatives all providing good to excellent yields and enantioselectivities. Achiral Rh­(I) catalysts were later applied to the synthesis of racemic products to expand upon the types of α-ketoamides, isatins, and α-branched aldehydes that could be employed …”
Section: Ketonesmentioning
confidence: 99%
“…The transition-metal-catalyzed hydroacylation of miscellaneous unsaturated hydrocarbons and carbonyl compounds involving aldehyde C–H bond activation has been recognized as one of the most robust and valuable organic transformations for direct C–C and C–O bond formation, and the products afforded therefrom have had an extraordinarily impressive impact on the research and development of original branded pharmaceuticals. In comparison with the substantially investigated hydroacylation reactions of alkenes, alkynes, and other conjugated unsaturated hydrocarbons for ketone synthesis, the complementary hydroacylation ultimately leading to ester products remains a less advanced reaction class, although several catalytic systems have been demonstrated that employ ketones as the starting materials . Consequently, the development of ketones and their counterparts for highly efficient and completely atom-economical hydroacylation would be both desirable and challenging.…”
mentioning
confidence: 99%
“… Over the last few decades, transparent efforts have been exerted on the highly efficient synthesis of these value-added esters by virtue of metal-catalyzed cross-coupling tactics (Scheme ). Classical intra- and intermolecular carbonyl hydroacylation in the presence of rhodium­(I), , nickel(0), ruthenium­(II), and samarium­(II) catalysis is one of the most comprehensively used approaches, and it constitutes a significant technology in the straightforward and atom-economical preparation of esters (Scheme a), albeit with inherent challenges yet to be overcome, such as the decarbonylation and aldol reactions. Alternatively, by taking advantage of the ruthenium(0) and palladium­(II) catalytic systems, the hydroesterification reactions of alkenes with formates can occur to afford the desired products through the activation of the formyl C–H bond (Scheme b).…”
mentioning
confidence: 99%
“…In a follow-up study, we prepared a novel dcpp-inspired bisphosphine ligand (L5) that contains two Pstereogenic centers. 50 This bidentate ligand for Rh expands the scope to include isatins and linear α-ketoamides with aliphatic aldehydes.…”
Section: Intermolecular Carbonyl Hydroacylationmentioning
confidence: 99%